Analisis Transformasi Digital Terhadap Efektivitas Pengawasan Koperasi dan Implikasinya Terhadap Perilaku Karyawan Pada Koperasi Sedana Ibu Wahini Tabanan - Jaya, I Ketut Aditya; Adriati, I Gusti. Ayu Wirati; Sari, Desak Made Febri Purnama; Martini, Ida Ayu Oka (Economic Reviews Journal, 2025)
This study aims to analyze the impact of digital transformation on the effectiveness of cooperative supervision and its implications for employee behavior at Koperasi Sedana Ibu Wahini Tabanan. The background of this study lies in the weakness of the cooperative’s internal supervision system, which is still conducted manually through conventional record-keeping and monitoring using CCTV, making it less effective in supporting organizational transparency and accountability. Digital transformation is viewed as a strategic effort to strengthen the supervisory function while fostering more disciplined, responsible, and adaptive employee behavior in response to technological developments. This research employs a descriptive qualitative approach, with data collected through semi-structured interviews, participatory observation, and documentation. Data analysis is carried out using an interactive model consisting of data reduction, data display, and conclusion drawing and verification. The findings indicate that the supervision system at Koperasi Sedana Ibu Wahini Tabanan remains manual through attendance recording and direct monitoring by management, resulting in supervision that is not yet optimal and difficult to measure objectively. Furthermore, the interview results show that employees and cooperative members demonstrate readiness and openness to adapting to the implementation of digital systems; however, support in the form of training is still needed to enhance their understanding of digital system usage. This study is expected to provide insights into the influence of digital transformation on supervision and employee behavior, as well as practical recommendations for cooperatives in designing appropriate digitalization strategies.